Taurine Deficiency Retinopathy in a Cat - Guberman, Úrsula Chaves [UNESP]; Merlini, Natalie Bertelis; Perches, Cintia Sesso [UNESP]; Gandolfi, Micaella Gordon [UNESP]; Nascimento, Bruna Menegate; de Sessa, Mariana [UNESP]; de Sousa, Juliana Marques [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP] (Universidade Federal do Rio Grande do Sul, 2023)
Background: Taurine is an essential amino acid for cats and its deficiency causes an ocular disorder called taurine deficiency retinopathy. The retinal lesion is definitive and can be classified into five progression stages. In an advanced stage, it leads to blindness that in most cases is irreversible. This disease is considered rare as taurine is currently supplemented in commercial cat food. The objective of this report is to describe the ophthalmic changes in a cat with advanced taurine deficiency retinopathy, a rare but current disease that is important for differential diagnosis of blindness in cats. Case: We report the case of an adult mixed-breed cat (weighing 3.4 kg), that was attended by the Ophthalmology Service of the College of Veterinary Medicine and Animal Science (UNESP - Botucatu), which was treated due to complaints of poor visual acuity for about 1 year. The animal, which was previously a stray animal, had been adopted for 2 years and provided premium cat food ad libitum. Ophthalmic examination showed bilateral mydriasis, with negative menace, direct pupillary, and consensual light reflexes. No change was observed in the ocular appendages, cornea, anterior chamber, lens, and vitreous humor. The eyes were normotensive and fluorescein test negative. Direct and indirect fundoscopy revealed an area of ellipsoidal hyperreflexia with darkened margins laterally to the optic nerve disk in the tapetal region and intense retinal vascular attenuation in both eyes, with a diagnosis of taurine deficiency retinopathy. Complete blood count and biochemical analysis parameters were within the normal range, including the leukocyte count. The guardian was instructed to continue feeding the cat balanced cat food and received information on the proper care and management of a blind animal. Discussion: Although taurine deficient retinopathy is currently underdiagnosed due to the supplementation of this amino acid in commercial cat food, animals that are not properly fed, such as those receiving dog food or homemade food, may be deficient in this amino acid. Taurine deficiency and in this case, the consequent taurine deficiency retinopathy, was diagnosed by visualizing the lesion characteristic of this amino acid deficit since no other retinal change presents this aspect in cats. Therefore, this lesion is considered pathognomonic of this deficiency. Hyperreflective retinal lesions with darkened margins indicate the slow chronic progression in the already stabilized lesions. The animal in this report presented pigmented lesion margins, indicating the chronicity of these retinal changes. Moreover, lesion signs are visible on fundoscopy only after a period of 2-11 months of nutritional amino acid deficiency, and complete retinal atrophy usually occurs after at least nine months of taurine deficiency. Thus, complete blindness associated with advanced retinal changes reinforced the suspicion that the animal had taurine deficiency for a prolonged period of time prior to its adoption. Its guardian was instructed to provide balanced commercial cat food, because although retinal lesions are irreversible, cardiac changes resulting from taurine deficiency are reversed with dietary supplementation. In addition, taurine deficiency affects other organs and systems, such as the central nervous, immune, and reproductive systems. In conclusion, although taurine deficiency retinopathy is currently rare, this condition should be considered one of the possible differential diagnoses for blindness in feline patients.
Retinopatia deficiente de taurina em uma gata
Keywords: amino acid; blindness; retina